The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00415-008-0816-8
|View full text |Cite
|
Sign up to set email alerts
|

The renin-angiotensin-aldosterone system in cerebral small vessel disease

Abstract: This exploratory study found no strong evidence for RAAS involvement in severe SVD in this population. The whole spectrum of SVD, including EC, MLI, and LA, can be considered as phenotypes for genetic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 38 publications
(46 reference statements)
0
34
1
Order By: Relevance
“…Increasing evidence has revealed the important role of local RAAS in CNS disorders. 8,9 Inhibitors of RAAS, which are widely used as antihypertensive drugs, may have potential beneficial and therapeutic effects on CNS disorders. We and others have shown that treatment with AT 1 receptor blockers can reduce the ischemic area in the brain and improve cognitive function in various animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has revealed the important role of local RAAS in CNS disorders. 8,9 Inhibitors of RAAS, which are widely used as antihypertensive drugs, may have potential beneficial and therapeutic effects on CNS disorders. We and others have shown that treatment with AT 1 receptor blockers can reduce the ischemic area in the brain and improve cognitive function in various animal models.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, accumulating evidence shows that RAAS that is localized in the CNS also has an important role in CNS disorders. 8,9 Recently, increased attention has focused on understanding the involvement of RAAS in the pathogenesis of neurodegenerative diseases. Kawajiri et al 10 observed a reduced Ang II level in the cerebrospinal fluid of patients with ALS.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter study, lower -344C allele frequency was linked with increased disease severity, which prompted speculation as to a possible protective nature of the -344C allele. 17 Another French study demonstrated that CYP11B2 TC and CC genotypes were associated with lower stroke index, 27 though not with blood pressure changes and gender-related contribution to C-344T effect was suggested. 27 These discrepancies may be explained by the difference in patient selection, evaluation of stroke severity, or ethnic differences.…”
Section: Regression Analysismentioning
confidence: 99%
“…26 A limited number of studies has addressed the contribution of CYP11B2 C-344T promoter variant to stroke pathogenesis, but with inconsistent findings. 17,27 The aim of the present case-control study was to examine whether C-344T CYP11B2 gene variant is associated with ischaemic stroke among Tunisians.…”
Section: Introductionmentioning
confidence: 99%
“…Patients presenting with SVD usually present in their later decades with often features suggestive of cognitive slowing, psychomotor withdrawal due to severe executive dysfunction described as difficulty to pay attention, retrieval defect, tip of the tongue phenomena, short term memory defects, and occasionally impaired judgement [16]. Gait and balance disturbances and falls are also major symptoms of patients with cerebral small vessel disease (SVD), and an important cause of morbidity and mortality in the elderly.…”
Section: Clinical Manifestationsmentioning
confidence: 99%